EVOLUSI TEORI FRAUD DAN RELEVANSINYA TERHADAP STRATEGI PENCEGAHAN FRAUD DANA DESA DI INDONESIA - Sinduk, Yohanes Frediski Sinduk (STIE Madani Balikpapan, 2025)
This study aims to analyze the phenomenon of village fund corruption in Indonesia. This study identifies that the modus operandi of corruption often involves fictitious projects, budget inflation, and budget cuts by village officials, which are triggered by the lack of supervision and community participation in the management of village funds. The methods used in this study are bibliometric analysis and Systematic Literature Review (SLR), which aim to identify trends, themes, and limitations in the existing literature on village fund fraud. The results of the study indicate that the perpetrators of corruption mostly come from village heads and their apparatus, with support from supra-village institutions that are often involved in corrupt practices. This study also highlights the importance of increasing supervision and community participation to prevent fraud in the management of village funds. Thus, this study is expected to contribute to formulating effective prevention strategies against village fund fraud, as well as providing a comprehensive picture of the development of similar research in Indonesia.